Given the function:
f(x) = 3x - 2
Let's find the inverse of the function f⁻¹(x).
To find the inverse of the function, apply the following steps:
• Step 1.
Rewrite y for f(x)
![y=3x-2](https://img.qammunity.org/2023/formulas/mathematics/high-school/cs951ld0m5fyz30f6jmmjk2jhieli70v8l.png)
• Step 2.
Interchange the x and y variables:
![x=3y-2](https://img.qammunity.org/2023/formulas/mathematics/college/b01xafeqciid0tzgtu98kyvovvm50tap3r.png)
• Step 3.
Solve for y.
Add 2 to both sides:
![\begin{gathered} x+2=3y-2+2 \\ \\ x+2=3y \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/6uppw5k799d2zhp2r1jblydetuh7rykyc6.png)
• Step 4.
Divide all terms by 3:
![undefined]()